Peran Digital Marketing Dalam Upaya Pengembangan UMKM “Jajan Burger” Di Kota Surakarta - Noviana Intan KP; Suprayitno Suprayitno; Syahrial Yoppi (Edumedia Solution, 2023)
Technological developments make digital marketing superior for increasing the sales of a business. The